2023
DOI: 10.1038/s41598-023-28399-1
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate screening mammography method for patients with breast implants

Abstract: In this study, we aimed to evaluate the benefits and losses of mammography with and without implant displacement (ID) and propose an appropriate imaging protocol for the screening of breasts with implants. We evaluated mammograms of 162 breasts in 96 patients including 71 breasts with biopsy-proven cancers. Mammography of each breast included standard MLO and ID MLO images. We reviewed the mammograms using clinical image quality criteria, which consist of parameters that evaluate the proper positioning of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Since a key factor to significantly influence mammography performance was the breast positioning, this should be prioritized as the central focus in mammography education. Other challenges are related to coping with pain and imaging of breast implants [11,12], and the need for further education. Metsälä et al [13] have shown that high quality in mammography services can be achieved via additional radiographer training.…”
Section: Introductionmentioning
confidence: 99%
“…Since a key factor to significantly influence mammography performance was the breast positioning, this should be prioritized as the central focus in mammography education. Other challenges are related to coping with pain and imaging of breast implants [11,12], and the need for further education. Metsälä et al [13] have shown that high quality in mammography services can be achieved via additional radiographer training.…”
Section: Introductionmentioning
confidence: 99%